Fetal middle cerebral artery Doppler in late-term pregnancy: a predicting factor for failed induction of labor. (18th October 2018) - Vannuccini, Silvia; Torricelli, Michela; Bocchi, Caterina; Severi, Filiberto M.; Di Tommaso, Mariarosaria; Petraglia, Felice
Abstract: Purpose: To study the role of fetal middle cerebral artery (MCA) Doppler evaluated prior to induction of labor in late-term pregnancies, in order to build an ultrasound-based predictive model for failed induction. Materials and methods: A prospective cohort study on 250 nulliparous women carrying singleton late-term pregnancies was conducted. Prior to induction, each patient underwent to an ultrasound evaluation for fetal MCA Doppler. Additional ultrasound parameters such as cervical length (CL), membranes thickness, amniotic fluid index, placental location, and estimated fetal weight (EFW) were collected. According to the type of response, women were divided into three groups: (A) responders within 24 h; (B) responders after 24 h, and (C) no responders. Results: Women who failed to enter active labor showed significantly higher fetal MCA pulsatility index (PI), longer CL and higher EFW. The estimated probability of logistic regression model combining the three variables achieved a sensitivity of 94.2% and a specificity of 86.36% (AUC, 0.926; 95% CI, 0.884 − 0.956, p < .0001) using as decision probability value the cut off >0.1838. Conclusions: In late-term pregnancies, an ultrasound-based model including cervical length, MCA PI, and EFW achieved a good accuracy in predicting those women who are likely to fail induction of labor.